Preliminary study-design of a piezoelectric floor energy harvester - Susilo, Sidik; Listijorini, Erny; Ahendyarti, Ceri; Febrianto, Ilham; Adhiwindoro, Akhmad (Jurnal Teknika, 2024)
A piezoelectric-based electrical energy harvesting device has been designed using a cantilever method that originates from mechanical pressure from humans climbing stairs. The method in this research uses an experimental method where there are variations in the load given by humans of 55 Kg, 65 Kg, and 75 Kg to provide force on an energy harvester that has 4 piezoelectric circuits installed, 38 of which are installed in series and parallel. piezoelectric, where the four circuits have a number of piezoelectrics of 10, 8, 10 and 8 piezoelectrics on each side. The resulting voltage will later be rectified using a rectifier bridge until it will be temporarily stored in the capacitor. The voltage is rectified using a rectifier bridge and stored in capacitors. The test was carried out in conditions where the respondent was walking leisurely and running. The results obtained without a rectifier circuit is 0.87 V, 1.06 V, 1.08 V. For a parallel circuit it is 0.78 V, 0.87 V, 0.96 V. In the rectifier circuit, it is obtained for a series circuit of 0.53 V, 0.66 V, 0.75 V. Electric current 0.01 mA, 0.03, 0.06 mA for parallel circuits 0.46 V, 0.78 V, 1.07 V and electric current 0.05 mA, 0.06 mA, 0.019 mA.